Hippocampus-Based Mitochondrial Respiratory Function Decline Is Responsible for Perioperative Neurocognitive Disorders - He, Keqiang; Zhang, Juan; Zhang, Wei; Wang, Sheng; Li, Dingfeng; Ma, Xiaolin; Wu, Xiaofan; Chai, Xiaoqing; Liu, Qiang (Frontiers in Aging Neuroscience, 2022)
Perioperative neurocognitive disorders (PNDs) are a type of cognitive dysfunction occurring with a higher incidence in elderly patients. However, the pathological mechanism of PND and effective treatment remain elusive. We generated a PND mouse model by providing wild-type mice with surgical trauma; in our case, we used tibial fracture to investigate PND pathology. Mice aged 7–8 months were randomly divided into two groups: the surgery (tibial fracture) group and the control (sham) group. All mice were subjected to anesthesia. We examined the transcriptome-wide response in the hippocampus, a brain region that is tightly associated with memory formation, of control mice and mice subjected to surgical trauma at day 1 and day 3 after the surgical procedure. We observed reduced transcript levels of respiratory complex components as early as day 1 after surgery, and subsequent protein changes were found at day 3 after surgical trauma. Consequently, the activities of respiratory complexes were reduced, and adenosine triphosphate (ATP) production was decreased in the hippocampus of mice with surgical operations, supporting that respiratory chain function was impaired. In support of these conclusions, the mitochondrial membrane potential (MMP) levels were decreased, and the reactive oxygen species (ROS) levels were significantly increased. Mechanistically, we demonstrated that surgery induced a significant increase in cytokine IL-1β levels at day 1 after surgery, which concomitantly occurred with transcript changes in respiratory complex components. We further uncovered that transcription factors PGC-1α and NRF-1 were responsible for the observed transcript changes in mitochondrial complex components. Importantly, HT22 cells treated with the cytokine IL-1β resulted in similar reductions in PGC-1α and NRF-1, leading to a reduction of both the transcript and protein levels of respiratory complex subunits. Consequently, respiratory function was impaired in HT22 cells treated with IL-1β. Taken together, we demonstrated that reductions in respiratory complex components and subsequent impairment in mitochondrial functions serve as a novel mechanism for PND pathology, providing a potential therapeutic target for PND treatment.